PENGARUH KOMITMEN DAN BUDAYA ORGANISASI BERBASIS INTEGRASI TERHADAP KINERJA DOSEN PADA PERGURUAN TINGGI KEISLAMAN: (The Effect of the Organizational Commitments And Cultural Organization Based on the Integration of Lecturers‟ Performance at Islamic College) - Dicki Hartanto (Perspektif Pendidikan dan Keguruan, 2016)
The aims of this paper is to find outh the effectivity of organization commitment andcultural organization based on theintegration of lecturers‟ performance at islamic Highereducation. The method of this paper applied was literature research by describing andanalyzing the effect of these two components in integrating the Islamic views. The paperresult showed that with the concept of integration in the organizational commitment andorganizational culture, the lecturers are expected to have a personality that has strongreligious beliefs and professional as well as performing scientific proffessional in scientificfields respectively at the instigation of their organizational commitment and organizationalculture based on the integration of the Islamic college.